Apakah Pengguna Filter Instagram Tidak Percaya Diri? : Ditinjau dari Citra Diri - Wulandari, Tasya Ayu; Mubina, Nuram; Leometa, Citra Hati (Universitas Muhammadiyah Metro, 2024)
In the current digital era, Instagram has become one of the most popular social media applications, especially with its filters that enhance photo results. These filters influence visual appearance and significantly impact psychological aspects, including self-confidence and self-image. This research aims to explore the influence of self-image on self-confidence among early adult women who use Instagram filters inKarawang Regency. The research methodology employed is quantitative with an associative causal design. Sampling is conducted using non-probability sampling via convenience sampling. The sample size of 160 participants is determined using the Lemeshow formula. Instruments used include a self-confidence scale based on theory and a self-image scale based on Jersild's theory, both constructed by the researcher. Hypothesis testing indicates a positive relationship between self-image and self-confidence. The coefficient of determination reveals that self-image contributes 48.8% to self-confidence.